Newborn Care Practices of Mothers in Arab Societies: Implication for Infant Welfare. (May 2019) - Arabiat, Diana H.; Whitehead, Lisa; AL Jabery, Mohammad A.; Darawad, Muhammad; Geraghty, Sadie; Halasa, Suhaila
Introduction: There are at least 22 Arab league states and sections in Northern Africa, southwestern Asia, and Europe that incorporate the vast Middle Eastern culture. The purpose of this study was to identify the cultural variations in newborn care practices, self-management of common illnesses, and their potential impact on infant welfare.Method: A qualitative design using a focus group approach with 37 Arab mothers in Jordan was used.Results: Findings revealed strong similarities in terms of beliefs, care practices, and the experience of intergenerational conflict in establishing and maintaining traditional practices among mothers. Potentially harmful practices included restrictive swaddling, rubbing a newborn's body with salt, and encouraging the ingestion of herbs in newborns.Discussion: It is important for nurses and midwives to be aware of traditional practices, cultural beliefs, and the implications for infant welfare if they are to effectively engage with families to promote the well-being of the newborn.